Clinico-epidemiological profile of severe acute malnutrition in infants below 6 months - Tiwari, Akanksha; Singh, Rupa Dalmia; Jain, Rakhi (International Journal of Contemporary Pediatrics, 2025)
Background: Severe acute malnutrition (SAM) is major public health burden, leading to significant morbidity and mortality. Early intervention during the first 1000 days of life is critical for influencing long-term health outcomes. This thesis aims to study clinico-epidemiological profile of SAM in infants under six months of age and to evaluate the outcomes after receiving facility-based care at NRC. Methods: The study is an observational prospective longitudinal study done in NRC of LLR Hospital, Kanpur including infants less than 6 months of age with SAM. Results: Out of 204 patients enrolled in the study, maximum percentage of patients were less than 2 months old. Male to female ratio was 1.27:1. SAM was more prevalent in infants with mixed feeding than Exclusive Breastfeeding. Low birth weight and the gestational age were associated with the occurrence of SAM. Other risk factors such as maternal illiteracy and family size were noted. Infants most commonly presented with lethargy followed by diarrhoea with dehydration and fever. Re-lactation was established in 56.7% of infants through Supplementary Suckling Technique (SST). Percentage of defaulters were 2% and death rate during NRC stay was 0.9%. 95% were discharged successfully from NRC, 66.9% were declared completely cured from NRC program on various follow up visits. 0.9%expired during the hospital stay and 2.9% infants expired after discharge. Conclusions: Lack of exclusive breastfeeding, inappropriate feeding practices, low birth weight, maternal illiteracy, increased family size are the common risk factors for SAM. Proper counselling of the mother can help in improving exclusive breastfeeding rate.